Effectiveness of an incentive policy intervention for rural health-care providers: a longitudinal survey in Shanghai. (October 2016) - Jing, Limei; Liu, Kun; Zhou, Xuhong; Wang, Li; Lou, Jiquan; Sun, Xiaoming
Abstract: Background: Grassroots health-care institutions in China are facing a shortage of professionals, especially general practitioners. To encourage health-care providers to come to and stay at rural grassroots institutions, Pudong New Area of Shanghai undertook a series of incentive reforms for rural health-care providers in July, 2014. We evaluated the effectiveness of incentive reform. Methods: The reform covered Pudong's 32 rural community health centres (CHCs): 12 remote rural CHCs, 11 general rural CHCs, and 9 suburban CHCs. The 13 urban CHCs in Pudong were not covered. The scheme included general practitioners, public health physicians, and other medical personnel. Motivators included eight aspects, such as bonus, promotion, and housing, of which bonus was the most important. Health-care providers in rural areas could get a monthly bonus of ¥1000–6000; general practitioners in remote rural CHCs received ¥6000. Quantity and statuses of community health-care providers for 2013–2015 were collected from 45 CHCs in the form of an institutional survey. Ethics approval was obtained from the ethics committee of Pudong Institute for Health Development. Findings: From December 31, 2013, to December 31, 2015, the total number of general practitioners in rural and suburban CHCs increased by 12·4%, from 799 to 898. The inflow of general practitioners increased by three times in remote rural CHCs (from 1 to 4), 1·2 times in general rural CHCs (from 6 to 13), and 0·6 times in suburban CHCs (from 14 to 22), and decreased by 52·5% (from 61 to 29) in urban CHCs. In 2015, the proportion of general practitioners as a share of health personnel was 19·8% (898 of 4528) in rural and suburban areas, an increase of 2·8 percentage points compared with 2013. The turnover rate of rural health-care providers decreased from 6·3% to 3·8% in these areas and from 11·8% to 6·5% in urban areas. Interpretation: With the financial incentives intervention, rural and suburban CHCs were more attractive to health-care providers, especially general practitioners. Furthermore, the stability of health-care providers was improved, especially in remote rural areas. However, the sustainability of financial subsidies and the policy depression effect, which means that there might be more inflow of health-care providers from other remote areas to Pudong and this will exacerbate the shortages of health personnel in and outside Shanghai, should be of concern in the long term. Funding: National Nature Science Foundation of China (#71503170) for data interpretation. Shanghai Municipal Commission of Health and Family Planning (#201540400, #201540134) for data collection and analysis.